2012
DOI: 10.1149/2.009203esl
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and Oxygen Reduction on Polycrystalline Platinum in Aqueous Tetramethylguanidine Alkaline Electrolyte

Abstract: Aqueous, 0.1 M 1,1,3,3-tetramethylguanidine was shown to be an active alkaline liquid electrolyte (without metal cations) using a polycrystalline platinum electrode. Cyclic voltammetry reveals that the electrolyte supports − OH conductivity, showing many platinum redox features observed in traditional electrolytes. Gradual reaction with H 2 O decreases ionic conductivity over several months. Oxygen reduction curves in TMG lack a distinct transition from kinetic to diffusion-limiting behavior due to organic ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…These experiments are closer to the conditions in APEFCs. These studies involved AEIs such a commercial QA types (Tokuyama AS-4) [145][146][147] in-house synthesised polysulfone-imidazolium types, 145 and a phosphonium type. 123d A more recent study investigated the effect of polymer backbone of QA-AEIs on the performance of an iron-cyanamide-derived catalyst.…”
Section: (Both Acid and Alkali) (10)mentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments are closer to the conditions in APEFCs. These studies involved AEIs such a commercial QA types (Tokuyama AS-4) [145][146][147] in-house synthesised polysulfone-imidazolium types, 145 and a phosphonium type. 123d A more recent study investigated the effect of polymer backbone of QA-AEIs on the performance of an iron-cyanamide-derived catalyst.…”
Section: (Both Acid and Alkali) (10)mentioning
confidence: 99%
“…145 Similarly, Konopka et al looked at the effect on the ORR of polycrystalline Pt of 1,1,3,3-tetramethylguanidinium cations. 146 Other studies have looked at the effect of AEIs themselves on the performances of various catalysts towards various reactions at high pH (where Naon® ionomer is not present). These experiments are closer to the conditions in APEFCs.…”
Section: The Need For Aeis In Electrochemical Systemsmentioning
confidence: 99%
“…Sluggish reaction kinetics with the alkyl ammonium hydroxide could be another reason for the inferior AMFC performance . Unlu et al reported that the anodic hydrogen desorption of Pt in quaternary ammonium hydroxide was 2.6 times slower than that in NaOH due to the specific adsorption of the cation .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies also found that the introduction of guanidine ion greatly improved the kinetics of oxidation and oxygen reduction catalyzed by Pt and carbon‐based non‐noble metals. [ 107 ]…”
Section: Guanidinium For Anion Exchange Membranesmentioning
confidence: 99%
“…Moreover, some studies also found that the introduction of guanidine ion greatly improved the kinetics of oxidation and oxygen reduction catalyzed by Pt and carbon-based non-noble metals. [107] Liu et al [104] grafted 2-benzyl-1,1,3,3-tetramethylguanidine (BBTMG) to bromomethylated PPO, and the large volume of guanidinium cations showed a higher alkaline stability (Figure 6g). Xue et al [108] synthesized four guanidine model compounds with different substituents, 1,1,2,2,3,3-hexaalkyl/ arylguanidinium chlorides (QGx, x = 1, 6, 12, and Ph), and studied the effects of these substituents on the alkaline stability of guanidine cations.…”
Section: Guanidinium For Anion Exchange Membranesmentioning
confidence: 99%